Metagenomic next-generation sequencing targeted and metagenomic next-generation sequencing for pulmonary infection in HIV-infected and non-HIV-infected individuals - Sun, Luyao; Zhang, Kaiyu; Liu, Yong; Che, Lihe; Zhang, Peng; Wang, Bin; Du, Na (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundWhen individuals infected with human immunodeficiency virus (HIV) experience pulmonary infections, they often exhibit severe symptoms and face a grim prognosis. Consequently, early, rapid, and accurate pathogen diagnosis is vital for informing effective treatment strategies. This study aimed to use metagenomic next-generation sequencing (mNGS) and targeted mNGS (tNGS) to elucidate the characteristics of pulmonary infections in HIV and non-HIV individuals.MethodsThis study enrolled 90 patients with pulmonary infection at the Department of Infectious Diseases of The First Hospital of Jilin University from June 2022 to May 2023, and they were divided into HIV (n=46) and non-HIV (n=44) infection groups. Their bronchoalveolar lavage fluid (BALF) was collected for mNGS analysis to evaluate the differences in pulmonary infection pathogens, and tNGS detection was performed on BALF samples from 15 HIV-infected patients.ResultsA total of 37 pathogens were identified in this study, including 21 bacteria, 5 fungi, 5 viruses, 5 mycobacteria, and 1 mycoplasma. The sensitivity of mNGS was 78.9% (71/90), which is significantly higher than that of conventional methods (CTM) (39/90, P=1.5E-8). The combination of mNGS with CTM can greatly enhance the sensitivity of pathogen detection. The prevalence of Pneumocystis jirovecii (82.6% vs. 9.1%), cytomegalovirus (CMV) (58.7% vs. 0%), and Epstein-Barr virus (EBV) (17.4% vs. 2.3%) was significantly higher in the HIV infection group than in the non-HIV infection group (P<0.05). Although no statistically significant difference was observed, the detection rate of Mycobacteria was higher in HIV-infected patients (17.4%) than in the non-HIV group (6.8%). Furthermore, the tNGS results of BALF from 15 HIV-infected patients were not entirely consistent with the mNGS results., and the concordance rate of tNGS for the detection of main pathogens reached 86.7% (13/15).ConclusionNext-generation sequencing (NGS) can accurately detect pathogens in the BALF of patients with pulmonary infection. The sensitivity of tNGS is comparable to that of mNGS. Therefore, this technique should be promoted in the clinic for better patient outcomes.